2018
DOI: 10.17719/jisr.2018.2971
|View full text |Cite
|
Sign up to set email alerts
|

Duygusal Zeka Ve Yaraticilik Arasindaki̇ İli̇şki̇ler: Üni̇versi̇te Öğrenci̇leri̇ Üzeri̇ne Bi̇r Çalişma

Abstract: Bu çalışmada üniversite öğrencilerinin duygusal zekâ düzeyleri ile yaratıcılık düzeyleri arasındaki ilişkinin tespit edilmesi temel amaç olarak belirlenmiştir. Bunun yanı sıra araştırmada öğrencilerin çeşitli demografik özellikleri ile duygusal zekâ düzeyleri ve yaratıcılık düzeyleri arasındaki ilişkiler incelenmiştir. Araştırma, Alanya Alaaddin Keykubat Üniversitesi Altso Turizm Meslek Yüksekokulu'nda öğrenim görmekte olan 393 öğrenci üzerinde yürütülmüş ve veriler anket tekniği aracılığıyla toplanmıştır. Ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…Büyüksalvarcı and Gündoğan [21] determined that the highest difference in all sub-dimensions of emotional intelligence was in favor of female students. In Akkan's study, it was determined that there was a significant difference in the sub-dimensions of optimism and benefiting from emotions in female students, but it was concluded that there was no significant difference in the expression of emotions sub-dimension [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Büyüksalvarcı and Gündoğan [21] determined that the highest difference in all sub-dimensions of emotional intelligence was in favor of female students. In Akkan's study, it was determined that there was a significant difference in the sub-dimensions of optimism and benefiting from emotions in female students, but it was concluded that there was no significant difference in the expression of emotions sub-dimension [21].…”
Section: Discussionmentioning
confidence: 99%
“…Büyüksalvarcı and Gündoğan [21] determined that the highest difference in all sub-dimensions of emotional intelligence was in favor of female students. In Akkan's study, it was determined that there was a significant difference in the sub-dimensions of optimism and benefiting from emotions in female students, but it was concluded that there was no significant difference in the expression of emotions sub-dimension [21]. In a few other studies in the literature [6], [21], [25], [26], [33], [34], [39]- [45] when the mean scores of emotional intelligence of the participants were examined according to gender, a difference was found in favor of female students in the studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bu durum çalışanların belirli bir entelektüel zekâ düzeyine sahip olmaları kadar, belirli bir duygusal zekâ düzeyine de sahip olmalarının çok önemli bir husus olduğunu göstermektedir (Yüksel, 2008). Çalışanların duygu ve düşüncelerinin yardımıyla duygusal dengesini sağlaması, duygusal zekâya sahip olması ve motive olması örgütlerin amaçlarını hayata geçirmelerine yardımcı olmak (Turhan ve Çetinsöz, 2019) ile birlikte çalışanların performansının yükselmesini (Asiamah, 2017;Çınar ve Özyılmaz, 2018;Ulutürk, 2021) ve bireylerde duygusal ve sosyal kapasitenin yüksek olması onların hem özel hem de mesleki alanlarında daha avantajlı bir konuma gelmelerini sağlayacaktır (Büyükşalvarcı ve Gündoğan, 2018). Bu doğrultuda, bireylerin hem iş hem de özel hayatta yaşanan çatışma düzeyindeki yoğunluk oranı ve negatif duyguları yönetmede ortaya çıkan güçlükler duygusal zekânın önemini arttımakta ve kavramı araştırma odağı yapmaktadır (Erdoğdu, 2008).…”
unclassified